Ultraluminous star-forming galaxies and extremely luminous warm molecular hydrogen emission at z = 2.16 in the PKS1138-26 radio galaxy protocluster - Ogle, P.; Davies, J.; Appleton, P.; Bertincourt, B.; Seymour, Nick; Helou, G. (2012)
A deep Spitzer Infrared Spectrograph map of the PKS 1138–26 galaxy protocluster reveals ultraluminous polycyclic aromatic hydrocarbon (PAH) emission from obscured star formation in three protocluster galaxies, including Hα-emitter (HAE) 229, HAE 131, and the central Spiderweb Galaxy. Star formation rates of ~500-1100 M ☉ yr–1 are estimated from the 7.7 μm PAH feature. At such prodigious formation rates, the galaxy stellar masses will double in 0.6-1.1 Gyr. We are viewing the peak epoch of star formation for these protocluster galaxies. However, it appears that extinction of Hα is much greater (up to a factor of 40) in the two ULIRG HAEs compared to the Spiderweb. This may be attributed to different spatial distributions of star formation-nuclear star formation in the HAEs versus extended star formation in accreting satellite galaxies in the Spiderweb. We find extremely luminous mid-IR rotational line emission from warm molecular hydrogen in the Spiderweb Galaxy, with L(H2 0-0 S(3)) = 1.4 × 1044 erg s–1 (3.7 × 1010 L ☉), ~20 times more luminous than any previously known H2 emission galaxy (MOHEG). Depending on the temperature, this corresponds to a very large mass of >9 × 106-2 × 109 M ☉ of T > 300 K molecular gas, which may be heated by the PKS 1138–26 radio jet, acting to quench nuclear star formation. There is >8 times more warm H2 at these temperatures in the Spiderweb than what has been seen in low-redshift (z < 0.2) radio galaxies, indicating that the Spiderweb may have a larger reservoir of molecular gas than more evolved radio galaxies. This is the highest redshift galaxy yet in which warm molecular hydrogen has been directly detected.